THE EFFECT OF THE PHET SIMULATION-ASSISTED THINK, TALK, WRITE LEARNING MODEL ON THE ABITILY OF STUDENTS’ CRITICAL THINGKING SKILLS ON PARABOLIC MOTION MATERIAL - Apriana, Erfan; Susanti, Ernita; Aripin, Aripin (PILLAR OF PHYSICS EDUCATION, 2025)
This research was motivated by the low ability of students to think critically in physics learning and the need for more innovation in the learning process. The researchers' efforts to overcome this problem are by applying the Think, Talk, Write learning model assisted by PhET Simulation. This research method is quasi-experimental with a non-equivalent control group design. The population in this study was class XI Physics students at a high school in Tasikmalaya, totaling 72 students. The data collection technique in this study describes the ability of critical thinking skills in as many as nine items. The data analysis techniques are prerequisite tests (normality and homogeneity tests), hypothesis tests, N-Gain, and model implementation analysis. The results of the analysis of hypothesis test data using the t-test at the significance level (α = 0.05) showed that after applying the Think, Talk, Write learning model assisted by PhET Simulation, we obtained 4.05 > 1.67, and the calculation results using SPSS showed sig results. (2-tailed) < 0.05 i.e. 0.000 < 0.05. Thus, Ha is accepted, and H0 is rejected. It means that it can be concluded that the Think, Talk, Write learning model assisted by PhET Simulation influences the ability of students' critical thinking skills on parabolic motion material in class XI Physics students at a high school in Tasikmalaya. These findings imply that integrating interactive technology into active learning models can yield better outcomes, suggesting the need for innovative teaching strategies to enhance education quality